The Role of People’s Spiritual Intelligence in The Relationship Between Love of Money and Happiness - Uray, Andrey Indra Maulana; Muhammad Zalviwan; Febrianawati (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
This research is important in understanding how human behavior is influenced by the intersection of materialistic values and happiness. The relationship between love of money and happiness often results in complex dynamics. Spirituality as a harmonizer offers a solution to manage the relationship between materialism and happiness. This study aims to explore how human spiritual intelligence can harmonize the love of money with the purpose of human life, namely, happiness. The method in this study uses a quantitative approach with analysis techniques using moderated regression analysis (MRA). The results of this study indicate that love of money has no significant effect on happiness, and spiritual intelligence strengthens the relationship between love of money and happiness.